Polyethersulfone-expanded graphite nanocomposites: charge transport and impedance characteristics - Ramanujam, B. T. S.; Mahale, Rajashree Y.; Radhakrishnan, S. (Composites Science and Technology, 2010)
Polyethersulfone (PES)-expanded graphite nanocomposites have been prepared by solution blending route after sonicating expanded graphite in dichloromethane. It has been observed that ultrasonication results in nanosheets formation leading to a low percolation threshold of 3 wt.%. At 5 wt.% filler loading the conductivity is of the order of 10(-2) S/cm. Hopping type of charge transport occurs at 3.2 wt.% expanded graphite in PES below which capacitive effects couple. The effective dielectric constant at low frequency increases with filler concentration. Impedance measurement has been carried out to evaluate interfacial capacitance which, for 3.2 wt.% expanded graphite addition in PES, increases to 110 pF from 32 pF for 1 wt.% expanded graphite in the polymer. DSC analysis shows an increment of 12 C in the T(g) of PES with 3 wt.% expanded graphite suggesting interaction between the polymer and filler. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Differential scanning calorimetry (DSC); Electrical properties; Modeling; Polymers; Scanning/transmission electron microscopy (STEM)

Polyphenylene sulfide- expanded graphite nanocomposites: processing route dependent electrical percolation - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, S. D. (Journal of Thermoplastic Composite Materials, 2017)
Polyphenylene sulfide (PPS)-expanded graphite (ExGr) conducting nanocomposites have been prepared by powder mixing and in situ polymerization routes after sonicating ExGr particles in acetone. Synthesized PPS has been used to make powder mixed composites. The powder mixed composites exhibit a percolation threshold of 3 wt% due to the formation of graphite nanosheets. When PPS-ExGr composites are prepared by in situ polymerization route, very low electrical percolation threshold less than 0.5 wt% ExGr is obtained. The low percolation threshold obtained is attributed to better dispersion of ExGr nanosheets in the polymer matrix when compared to powder mixed composites. The synthesized PPS has been characterized by X-ray diffraction, differential scanning calorimetry, and infrared spectroscopy. The formation of graphite nanosheets has been confirmed by transmission and scanning electron microcopy analysis.

Polypropylene-based conducting nanocomposites: effect of aspect ratio of second conducting filler on the electrical percolation - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, S. D. (Journal of Thermoplastic Composite Materials, 2017)
Powder-mixed polypropylene (PP)-graphite binary composites exhibit an electrical percolation threshold at 10 wt% graphite signifying insulator-semiconductor transition. Three conducting fillers such as carbon black (CB), sonicated expanded graphite (s-ExGr), and carbon nanofiber (CNF) are mixed with PP-7 wt% graphite binary composites. The electrical percolation threshold has been found to have inverse relation to the aspect ratio of second conducting fillers in hybrid composites. The aspect ratio of second conducting fillers varies in the order CB < ExGr < CNF. The electrical percolation threshold is found to vary for the hybrid composites as 2.2 wt% for CB addition, 0.75 wt% for ExGr addition, and 0.2 wt% for CNF addition in the PP-7 wt% graphite binary composites. When the aspect ratio of second conducting fillers increases, they reduce the barrier for the charge transport. The second conducting fillers occupy the interspace of graphite and alternating current studies show that the effective dielectric constant increases with the concentration of second conducting filler in the hybrid composites. The composites are characterized by transmission electron microscopy and scanning electron microscopy. Melt-crystallized PP-7 wt% graphite-CNF composites exhibit higher percolation threshold due to decrease in the polymer viscosity which increases the interparticulate distance.
Keywords: carbon nanofiber; Conducting polymer composites; Electrical properties; graphite nanosheets; hybrid composites; percolation; scanning; transmission electron microscopy